Strengthening the Value of Religious Moderation in the Era of Society 5.0 - Reza Fauzi; Luthfi Yasykur; Mahmud Mahmud; Mohamad Erihadiana (EDUTEC : Journal of Education And Technology, 2024)
Indonesian people who are multi-religious are prone to act intolerantly towards religious people and do not use religion as an inspiration in social life but as an aspiration. In addition to an understanding of religious moderation in a multicultural society, Indonesia is faced with the challenges of the 5.0 era of society. where people experience changes to a new life based on information technology. The purpose of this study is to obtain an overview of religious moderation. In addition, this research also aims to provide insights related to strengthening religious moderation amid an information society in the era of Society 5.0. This study used a qualitative approach using library research. The results show that strengthening religious moderation cannot be separated from the value of tolerance. The era of society 5.0 is increasingly open to information about various kinds of different views and understandings of religion. It takes an attitude of tolerance both passively and actively. Passive tolerance is carried out with an attitude of respect, and respect for differences, while tolerance is active, namely communicating both in the real world and the virtual (digital) world, building togetherness, and collaborating in the life of Society 5.0.